Synagogen in Göttingen - Aufbrüche und Abbrüche jüdischen Lebens - Schaller, Berndt (2017)
The book "Synagogues in Göttingen: departures and ceasing of Jewish life," deals with the 700-year history of Jewish life in Göttingen and the various synagogues that have been existing since the beginning of the 14th Century. This is the 2nd, revised and expanded edition.The book "Synagogues in Göttingen: departures and ceasing of Jewish life," deals with the 700-year history of Jewish life in Göttingen and the various synagogues that have been existing since the beginning of the 14th Century. This is the 2nd, revised and expanded edition...